Microraptor reveals specialized gliding capabilities in multiwinged early paravians - Csaba Hefler; Ying Wang; Xiaoli Wang; Xiaoting Zheng; Thomas G. Kaye; Maxime Grosmougin; Matthieu Chotard; Luke Barlow; Huihe Qiu; T. Alexander Dececchi; Michael B. Habib; Wei Shyy; et al. (Proceedings of the National Academy of Sciences, 2026)
Agile and efficient modern flyers like birds and insects rely on complex aerodynamics to increase performance such as leading edge vortices, tip vortices, rapid pitch rotations as well as wing–wake and wing–wing interactions. However, their evolutionary origins are poorly understood. Early birds and their closest relatives like Microraptor had a multiwinged configuration featuring long pennaceous feathers on their arms, legs, and tail, a configuration not seen today. The skill of these early flyers has been debated, centering around what was driving the evolution of this multiwing configuration and its loss in favor of the modern two-winged configuration. In this context, the aerodynamics and wing–wing interactions of Microraptor during gliding flight are investigated. The gliding flight mechanics of Microraptor exhibit flow patterns consistent with those observed and quantitatively assessed in volant living animal species. We analyze leading edge vortices on the forewing and hindwing including beneficial wake interactions between them as well as tip vortices on the distinct distally flared hindwing. The latter is unique in Microraptor as the hindwing’s characteristic outer span flare provides the necessary surface for the tip vortex to be bound to and thus contribute additional lift. These findings suggest that Microraptor evolved toward utilizing leading edge and tip vortices and their aerodynamic interactions. This implies that such utilization was also being exploited by other early multiwinged theropods to differing extents as part of a crucial milestone in early flight evolution.